PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA FUNDAMENTAL, KINERJA SAHAM DAN NILAI PERUSAHAAN - Harry Santoso; Roy Sembel; Gracia Shinta S. Ugut; Edison Hulu (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
This study aims to understand the influence of good corporate governance onfundamental firm performance, stock performance, and firm value of companiesconsistently included in IICD annual report for 5 years in 2014-2018. The goodcorporate governance is proxied by using the score of ASEAN corporategovernance scorecard published in the firm annual report. A total of 11 sampleswere collected using purposive sampling method and analyzed using panel dataregression. The results show that the good corporate governance does not havesignificant influence on the fundamental firm and stock performance. However,it has significant influence on the firm value.